Percutaneous thrombectomy in the management of early rethrombosis in venous thoracic outlet syndrome: two case reports - Ján Sýkora; Kamil Zeleňák; Martin Vorčák; Adam Krkoška; Štefánia Vetešková; Martina Sýkorová; Jozef Sivák; Ľuboš Hlinka; Igor Šinák (CVIR Endovascular, 2021)
Abstract Background Venous thoracic outlet syndrome resulting in the upper limb deep venous thrombosis is known as Paget–Schroetter syndrome or effort thrombosis. A general treatment algorithm includes catheter-directed thrombolysis followed by surgical thoracic outlet decompression. There are limited data regarding endovascular treatment of rethrombosis presenting early after the surgery. Case presentation Two cases of early rethrombosis successfully treated with percutaneous mechanical thrombectomy by two different techniques are described. In both cases, rethrombosis was diagnosed soon after thrombolysis and first rib resection with scalenectomy. After 12 months, both patients remain symptom-free, with patent subclavian veins confirmed by duplex ultrasonography. Conclusion Percutaneous mechanical thrombectomy devices may offer a safe treatment option for patients with recurrent thrombosis after thoracic outlet surgery, even when thrombolytic therapy is contraindicated.